Pan-SARS neutralizing responses after third boost vaccination in non-human primate immunogenicity model. Issue 9 (23rd February 2022) - Kalnin, Kirill V.; Plitnik, Timothy; Kishko, Michael; Huang, Dean; Raillard, Alice; Piolat, Julie; Anosova, Natalie G.; Tibbitts, Timothy; DiNapoli, Joshua; Karve, Shrirang; Goldman, Rebecca; Gopani, Hardip; et al.
Highlights: No breadth against VoC attained with heterologous sequences in primary vaccination. Boosting with original vaccine results in breadth against VoC and SARS-CoV-1. Neutralizing breadth after boost is independent of vaccine sequence or modality. Pan-corona neutralizing effect is achieved with third dose of the original vaccine. Abstract: The emergence of SARS-CoV-2 variants, especially Beta and Delta, has raised concerns about the reduced protection from previous infection or vaccination based on the original Wuhan-Hu-1 (D614) virus. To identify promising regimens for inducing neutralizing titers towards new variants, we evaluated monovalent and bivalent mRNA vaccines either as primary vaccination or as a booster in nonhuman primates (NHPs). Two mRNA vaccines, D614-based MRT5500 and Beta-based MRT5500β, tested in sequential regimens or as a bivalent combination in naïve NHPs produced modest neutralizing titers to heterologous variants. However, when mRNA vaccines were administered as a booster to pre-immune NHPs, we observed a robust increase in neutralizing titers with expanded breadth towards all tested variants, and notably SARS-CoV-1. The breadth of the neutralizing response was independent of vaccine sequence or modality, as we further showed either MRT5500 or recombinant subunit Spike protein (with adjuvant) can serve as boosters to induce broadly neutralizing antibodies in the NHPs primed with MRT5500. The data support the notion that a third vaccination is key to boosting existing titers and improving the breadth of antibodies to address variants of concern, including those with an E484K mutation in the Receptor Binding Domain (RBD) (Beta, Gamma).